IS THE PHENOMENON POLITICAL CONSUMPTION OVERRATED? - UNCOVERING POLITICAL INTENTIONS AND VALUES OF ORGANIC FOOD CONSUMPTION - Grunbaum, Niels Nolsoe; Stenger, Marianne (European Scientific Journal, ESJ, 2015)
The aim of this paper is to create a more complex and holistic understanding of the value system of the political consumer. A case study was undertaken were the unit of analysis constituted 12 high users of organic food products. The empirical data was analysed by utilizing Reynolds and Gutman’s laddering technique. The results revealed that the purposive selected informants activate different cognitive structures when buycotting organic food. In other words, the informants activate different values for similar attributes and consequences. This means that consumption of organic food is related to different value sets. That is, value sets where the political aspects are represented to different degrees. This means that some informants primarily buycott organic food for personal or family related reasons. For this group of informants, the focus is mainly on health related issues. Preservation of nature or environmental concern is important in the sense that it in the end relates to promoting personal security and health. This means that the environmental aspect cannot automatically be assumed to be a political motive when buycotting organic food, because it can be linked to personal motives. Understanding environmental issues solely as political motives thus reflects a rather mundane understanding. Further and more problematic it also leads to wrong results when trying to investigate the extent of political consumption from a positivistic paradigmatic posture.More specifically, survey studies will have a tendency to conclude that the phenomenon i.e. political consumption is much more prevalent than it actually is. The novel findings yield theoretical as well as practical implications. For practitioners a more comprehensive understanding of consumer values related to “politicized” products or services will enable companies to better understand consumers need and expectations. The latter being a necessity if confirmation of expectations, satisfaction, retention of customers and customer loyalty are goals of importance for the selling company.